Information Literacy Advocacy—Woody's Ten Commandments - Horton, Forest Woody (Library trends, 2011)
The author focuses on the importance of the role of the advocate for information literacy practitioners who are given the responsibility of introducing information literacy programs and projects into their organizations—whether as a teacher in an educational context, a teacher in a private sector company context, a policy official in a government program context, or in some other context. The article first traces many of the most important events that led to the information literacy concept historically so that the reader will have some background before coming to the "ten commandments," a term the author uses to embrace the lessons he has learned over the years, which are relevant to an advocate's role. In this regard, the author places the concept in an international context, pointing out the key role UNESCO has played, in part because he was directly involved in most of those seminal activities as an organizer and facilitator. Each of ten lessons learned is then taken up briefly, not in any particular order, using an informal and easy-to-understand writing style. One important goal of the article is to emphasize that because information literacy is a relatively "new" concept in the formal sense (albeit under many different labels and terms it has been around for a very long time), and because it uses two words —"information" and "literacy"—that are themselves subject to many different and often confusing interpretations, virtually every information literacy practitioner, even professional librarians very familiar with the concept, too often assume that their audiences, constituents, and clients will readily understand the concept. In the author's view, that is simply not the case, and therefore the added role of becoming an advocate, not just a teacher, is extremely important if the practitioner is to be successful.